Gradual polyploid genome evolution revealed by pan-genomic analysis of Brachypodium hybridum and its diploid progenitors - Sean P. Gordon (Nature Portfolio, 2020)
Existing plant pan-genomic studies usually report considerable intraspecific whole gene presence-absence variation. Here, the authors use pan-genomic approach to reveal gradual polyploid genome evolution by analyzing of Brachypodium hybridum and its diploid progenitors.